REVIEW ON COMPLEMENTARY AND ALTERNATIVE MEDICINE (CAM) IN ORAL HEALTH (International Journal of Ayurveda and Pharma Research, 2020)
Background: Complementary and Alternative Medicine (CAM) is a cluster of heterogeneous medical and health care systems, practices and products that can be used along with conventional medicine. This review article is about CAM system that is being used in oral health, challenges of such uses and the need for global regulations while using CAM products as medicines.Discussion: These systems are integral part of culture. Ayurvedic therapies are used for alleviating various oral conditions. Herbal mouth rinses and dentifrices are used for plaque control which is the basic process in oral care. Though deficiency exists regarding reports of controlled studies of Homeopathic medicines in pain conditions, Homeopathy is effective in the treatment of idiopathic trigeminal neuralgia. Last decade had witnessed an increasing interest in medicinal plants thereby promoting them as alternatives to standard conventional medicines.These therapeutics are gaining importance in a global scale. Limited access to conventional oral care, lower costs and general belief of minimal toxicity enhances the use of Ayurveda, Herbal and Homeopathic medicines and therapies in oral diseases. Budgetary allocations for this traditional system care of different countries, designing research programs to focus on traditional medicines and implementation of laws for propagation of CAM systems reflects the global inclination towards this system of healthcare.Conclusion: Considering the broadened scope of CAM therapeutics in dental healthcare, it is recommended that a dental professional be consulted prior to using these products in an attempt to reduce the probability of side effects or drug interactions.